NcRNA-regulated CAPZA1 associated with prognostic and immunological effects across lung adenocarcinoma - Qin, Tingting; Xiang, Wanping; Mao, Yiming; Zhai, Hongyan; Yang, Zhihao; Zhang, Hongpan (Frontiers in Oncology, 2023)
Recently, extensive discoveries have suggested that the F-actin capping protein α1 subunit (CAPZA1) in various human tumors could elicit significantly important parts in regulating cell proliferation, metastasis and epithelial‐mesenchymal transition. However, the immune-regulating role of CAPZA1 in the initiation and development of Lung adenocarcinoma (LUAD) remains incompletely clear. In our research, we firstly found that CAPZA1 serves as an oncogene in pan-cancers from TCGA data and higher CAPZA1 expression process unfavorably prognostic value in LUAD based on Starbase database and PrognoScan database. Then, in our analyses, lncRNAs AC026356.1 in LUAD acts as a competitive endogenous RNA (ceRNA) of miR-30d-5p, which might be the possible regulatory miRNA of CAPZA1 based on the Starbase database. Finally, we confirmed that CAPZA1 expression had a tightly positive correlation with immune infiltration cells, immune infiltration markers, TMB, MSI, immune score, stromal score, and immune checkpoints, indicating that CAPZA1 was a markedly reliable therapeutic target for immunological antitumor strategy. In conclusion, our investigations unveiled that CAPZA1 might function as an immune-associated biomarker in the development and treatment of LUAD, thereby acting as a promising prognostic and therapeutic target against LUAD.